Electrical Stimulation Prevents Preferential Skeletal Muscle Myosin Loss in Steroid-Denervation Rats - Yamada, Takashi; Himori, Koichi; Tatebayashi, Daisuke; Yamada, Ryotaro; Ashida, Yuki; Imai, Tomihiro; Akatsuka, Masayuki; Masuda, Yoshiki; Kanzaki, Keita; Watanabe, Daiki; Wada, Masanobu; Westerblad, Håkan; et al. (Frontiers in Physiology, 2018)
Severe muscle weakness concomitant with preferential depletion of myosin has been observed in several pathological conditions. Here we used the steroid-denervation (S-D) rat model, which shows dramatic decrease in myosin content and force production, to test whether electrical stimulation (ES) treatment can prevent these deleterious changes. S-D was induced by cutting the sciatic nerve and subsequent daily injection of dexamethasone for 7 days. For ES treatment, plantarflexor muscles were electrically stimulated to produce four sets of five isometric contractions each day. Plantarflexor in situ isometric torque, muscle weight, skinned muscle fiber force, and protein and mRNA expression were measured after the intervention period. ES treatment partly prevented the S-D-induced decreases in plantarflexor in situ isometric torque and muscle weight. ES treatment fully prevented S-D-induced decreases in skinned fiber force and ratio of myosin heavy chain (MyHC) to actin, as well as increases in the reactive oxygen/nitrogen species-generating enzymes NADPH oxidase (NOX) 2 and 4, phosphorylation of p38 MAPK, mRNA expression of the muscle-specific ubiquitin ligases muscle ring finger-1 (MuRF-1) and atrogin-1, and autolyzed active calpain-1. Thus, ES treatment is an effective way to prevent muscle impairments associated with loss of myosin.